2006
DOI: 10.1093/annonc/mdl287
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid transcription factor 1—a new prognostic factor in lung cancer: a meta-analysis

Abstract: TTF-1 is a good prognostic factor for survival in NSCLC. Its effect appears also significant when the analysis is restricted to patients with adenocarcinoma. This study supports the fact that TTF-1 could be included in further prospective trials studying prognostic factors in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 23 publications
12
112
0
Order By: Relevance
“…Two other studies (Haque et al, 2002;Tan et al, 2003), evaluated stages I-IIIA NSCLCs with long-term follow-up and found that patients with strong Nkx2-1 expression had significantly better survival than patients with no Nkx2-1 (P=0.0067). A meta-analysis (Berghmans et al, 2006) using ten related studies published in the lung cancer literature showed that Nkx2-1 positivity was indeed significantly associated with better survival in NSCLC patients, and especially with early and locally advanced stages and in ADC.…”
Section: Prognostic Role Of Nkx2-1 In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies (Haque et al, 2002;Tan et al, 2003), evaluated stages I-IIIA NSCLCs with long-term follow-up and found that patients with strong Nkx2-1 expression had significantly better survival than patients with no Nkx2-1 (P=0.0067). A meta-analysis (Berghmans et al, 2006) using ten related studies published in the lung cancer literature showed that Nkx2-1 positivity was indeed significantly associated with better survival in NSCLC patients, and especially with early and locally advanced stages and in ADC.…”
Section: Prognostic Role Of Nkx2-1 In Lung Cancermentioning
confidence: 99%
“…In the advanced tumor stage, negative Nkx2-1 expression was an independent and significant marker for poor prognosis (Hiramatsu et al, 2010). Several other studies also evaluated the prognostic role of Nkx2-1 expression in NSCLC (Haque et al, 2002;Au et al, 2004;Berghmans et al, 2006), especially in lung ADC (Stenhouse et al, 2004;Barlési et al, 2005).…”
Section: Prognostic Role Of Nkx2-1 In Lung Cancermentioning
confidence: 99%
“…TTF-1 is highly sensitive and specific for the diagnosis of primary lung cancer. TTF-1 is a transcription factor that is specifically expressed in the thyroid and lungs, present in 60-70% of pulmonary adenocarcinomas; therefore, this marker is useful for distinguishing between primary and metastatic lesions [6,7]. ACC developing in the salivary glands is reported to exhibit a better prognosis than other pathological types of carcinoma occurring in the salivary glands, due to its slow growth and absence of metastasis until the late stages of tumor development [8].…”
Section: Discussionmentioning
confidence: 99%
“…A peripheral tumor usually presents as a solitary pulmonary nodule/mass on plain films or chest CT. A rounded opacity with an irregular border (lobulation, notching and infiltrating edges) and cavitation within the mass are the signs of peripheral primary carcinoma [6]. Serum tumor markers, e.g., NKX2-1 (NKX homeobox-1 gene), also known as TTF-1 (thyroid transcription factor-1) can be considered as a transcription factor for development, diagnosis and prognosis of lung cancer [7]. Risk factors for the development of acute spontaneous tumor lysis syndrome in patients with nonhematological solid tumors include large tumor burden ([10 cm) with necrosis, rapidly proliferating tumor, extensive bone marrow involvement, hepatic metastasis, elevated white cell count ([50000/ll), elevated lactate dehydrogenase level, use of potentially nephrotoxic drugs and drugs which inhibit uric acid excretion, elevated uric acid level, impaired renal function, extrinsic compression of the urinary tract by the tumor, underlying problems such as dehydration, infection or urinary obstruction.…”
Section: Discussionmentioning
confidence: 99%